Application of Hydrothermal Altered Reservoir Identification Method in Metamorphic Rock Buried Hill of Bozhong sag, Bohai Bay Basin, China - Zhu, Boyuan; Pan, Renfang; Zhang, Chaomo; Zhang, Zhansong; Shi, Wenrui (Frontiers in Earth Science, 2022)
Hydrothermal fluid is one of the factors controlling Archean buried hill reservoirs in Bozhong 19-6. However, there are no clear studies focusing on the influence of hydrothermal alteration products and their lithological characteristics on reservoirs. Through alteration reservoir characterization and construction of a new logging-rock mechanics alteration degree difference model, the comprehensive use of core, thin section, and electrical imaging logging data, and with metamorphic and igneous rocks as the research objects, the relationship between lithologies with different alteration degrees and reservoir quality is revealed; this provides a reference for a more comprehensive understanding and evaluation of the reservoir. This study shows that feldspar chloritization and sericitization are the main factors controlling the hydrothermal alteration of the reservoir; the overall alteration degree of igneous rocks is high, and the overall alteration degree of metamorphic rocks is low; the reservoir with strongly altered igneous facies is prone to forming dissolution pores, with strong reservoir inhomogeneity and poor reservoir performance, and the alteration degree (Izby) is greater than 15%; the reservoir with weakly altered metamorphic facies is prone to developing fractures, and the high reservoir productivity and alteration degree (Izby) is 0. The reservoirs with altered metamorphic facies have a large formation number and various spatial types. The reservoir quality is second only to the reservoirs with weakly altered metamorphic rock facies, and the alteration degree (Izby) ranges from 0% to 15%.